Mobilidade urbana: O Brasil em transformaç\~ao. O papel do IPEA na construç\~ao do Pacto da Mobilidade - Vicente Correia Lima Neto; Carlos Henrique Ribeiro de Carvalho; Renato Nunes Balbim (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This text focuses on the Brazilian mobility sector. It is discussed aspects of the National Urban Mobility Policy (PNMU) and the current distribution of traveling modes in Brazilian cities. It is also presented on this text a tree of mobility problems and a range of possible solutions, in order to find a match of each problem and solution. It is also a goal of this paper assists the search for references and detailing the solutions for public policy proposal.
Keywords: R42; R48; R49; 330; Mobility Pact; National Urban Mobility Policy; Externalities